Cognitive assessment in preterms by Bayley-III: development in the first year and associated factors - Suelen Rosa de Oliveira; Ana Carolina Cabral de Paula Machado; Lívia de Castro Magalhães; Débora Marques de Miranda; Jonas Jardim de Paula; Maria Cândida Ferrrez Bouzada (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To analyze the cognitive development of preterm infants at six and 12 months of corrected age and the associations with perinatal and socioeconomic factors. Methods: Cognitive development of 40 infants (20 preterm and 20 full-term) at six and 12 months of age was evaluated using the Bayley-III scale. Correlations between cognitive outcome and associated factors were assessed using Spearman correlation. Stepwise multiple linear regression analysis with covariance was applied to identify changes on cognitive score between six and 12 months. Results: Bayley-III cognitive score in preterm group was significantly lower than in full-term group at both six and 12 months of age. Birth weight correlated with cognitive performance at six months and head circumference at birth at 12 months, in full-terms infants. The occurrence of necrotizing enterocolitis was inversely associated with cognitive score in preterms at 12 months. An increase in cognitive score was observed between six and 12 months in both groups, but the gain was more pronounced in preterms. Conclusions: These findings suggest some cognitive recovery capacity in the first year despite the restrictions imposed by premature birth and emphasize the importance of early interventions in this population.